ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI PEMERINTAHAN NOMOR 07 TENTANG AKUNTANSI ASET TETAP PADA ASET TANAH PEMERINTAH PROVINSI KALIMANTAN BARAT - B51109126, RIZKA ANSHARIA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
According to Government Accounting Standards (GAS) in Indonesia, the government recognizes the fixed assets if there is evidence that there has been a title transfer and/or legal control. Accounting for fixed assets has been regulated in Government Accounting Standard - Statement No. 07. Reliability of land reported in financial statement is a must, due to administrative regulation and anticipation of legal risk. This research paper aims to determine the implementation of GAS Statement No. 07: Accounting for Fixed Assets in Provincial Government of West Kalimantan, particularly the reliability of the recognition of land assets, and efforts made by Financial and Assets Management Board (BPKAD) of West Kalimantan on its responsibility of assets administration, especially in order to improve the reliability of the recognition of land assets. The result showed 98.78% of the total land assets reported on Balance Sheet of the Provincial Government of West Kalimantan as December 31, 2015 had certificate on behalf of the Provincial Government of West Kalimantan, the indication of high reliability. Keywords: PSAP No. 07, Accounting for fixed assets